Humor as correlates to stress among selected college students: basis for a Guidance Intervention Program - Quennie Philina M. Ochoa. 4 0 16; 5 (2017)
u
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2